(untitled) - Hans Mohr (New York, 1995)
The book offers comprehensive treatment of the plant physiology. It begins with a detailed study of the cell as the basis for plant function, followed by the metabolic processes of photosynthesis and respiration. The book's 33 chapters also treat energy flow, differentiation, reproductive development, hormone action, regenerative potential, water relations and transport, movement, stress response, and crop physiology. This book features nearly 700 illustrations of exceptional clarity, uses SI units throughout, and highlights applied aspects of plant physiology processes
Keywords: plant physiology